Isoflavone, Nutrients Intake and Stress Level To Premenstrual Syndromes - Zaddana, Cantika (Journal of Science Innovare, 2018)
Menstruation is a characteristic of puberty in adolescent girls. Adolescent girls often have complaints of premenstrual syndrome (PMS) that is characterized by a collection of physical and psychological symptoms which occur in 7 to 10 days before menstruation. Studies have shown that there are several ways to relieve PMS. Therefore, the main objective of this study was to analyze isoflavone, nutrients intake, and stress level to Premenstrual Syndromes in adolescent girls in Bogor, West Java. The study was conducted on 100 girls aged 15-16 years at two high schools in Bogor. This present study showed that the majority of adolescent girls had PMS which most of them suffered severe symptoms. Results showed that the isoflavone and nutrients intake were not significantly associated with premenstrual syndromes. Stress level had a positive correlation to the PMS but did not seem to be a risk factor to PMS. Howefer, this implies that controling stress is important so that young women can avoid severe premenstrual syndromes. Keywords: Adolescent Girls, Isoflavone, Nutrients, Stress, Premenstrual Syndromes